Sequential Emergence and Wide Spread of Neutralization Escape Middle East Respiratory Syndrome Coronavirus Mutants, South Korea, 2015 - Yeon-Sook Kim; Abdimadiyeva Aigerim; Uni Park; Yuri Kim; Ji-Young Rhee; Jae-Phil Choi; Wan Beom Park; Sang Won Park; Yeonjae Kim; Dong-Gyun Lim; Kyung-Soo Inn; Eung-Soo Hwang; et al. (Emerging Infectious Diseases, 2019)
The unexpectedly large outbreak of Middle East respiratory syndrome in South Korea in 2015 was initiated by an infected traveler and amplified by several “superspreading” events. Previously, we reported the emergence and spread of mutant Middle East respiratory syndrome coronavirus bearing spike mutations (I529T or D510G) with reduced affinity to human receptor CD26 during the outbreak. To assess the potential association of spike mutations with superspreading events, we collected virus genetic information reported during the outbreak and systemically analyzed the relationship of spike sequences and epidemiology. We found sequential emergence of the spike mutations in 2 superspreaders. In vivo virulence of the mutant viruses seems to decline in human patients, as assessed by fever duration in affected persons. In addition, neutralizing activity against these 2 mutant viruses in serum samples from mice immunized with wild-type spike antigen were gradually reduced, suggesting emergence and wide spread of neutralization escapers during the outbreak.